Modular assembly of porous organic cage crystals: isoreticular quasiracemates and ternary co-crystal - Tothadi, Srinu; Little, Marc A; Hasell, Tom; Briggs, Michael E.; Chong, Samantha Y.; Liu, Ming; Cooper, Andrew I. (CrystEngComm, 2017)
Small changes in molecular structure and crystallisation conditions can have a profound effect on the crystal packing of molecules. Increasing the system complexity-for example, by introducing multiple components-greatly increases the number of potential outcomes. Hence, the rational design of porous cocrystals with multiple components is challenging. Here, we report a family of isoreticular quasiracemate crystalline phases for porous organic cages, FT-RCC3-R center dot CCX-S (where X = 1, 2, or 4), that were prepared in a modular and predictable fashion. By using directional intermolecular interactions between cages, we were able to prepare a rare ternary co-crystal, (CC3-S(0.5)CC4-S-0.5)center dot(CC13-S(0.5)CC3-S(0.25)CC4-S-0.25).
Keywords: cocrystals; Frameworks; Gas-chromatography; Halogen Bonds; Hydrogen-bonds; Molecular Cage; Nanoparticles; Pores; porosity; Separation

Morphological evolution of two-dimensional porous hexagonal trimesic acid framework - Tothadi, Srinu; Koner, Kalipada; Dey, Kaushik; Addicoat, Matthew; Banerjee, Rahul (ACS Applied Materials & Interfaces, 2020)
Hexagonal single crystal structure (Form II) of trimesic acid (TMA) has been isolated by dissolving the interpenetrated Form I of TMA in tetrahydrofuran. Form II (hexagonal) was converted to Form I (interpenetrated) at room temperature through some intermediate structures. A detailed time-dependent FESEM study shows that the external morphology of Form II (hexagonal) is a hollow hexagonal tube that mimics its crystal structure. The block-shaped (morphology) of Form I (interpenetrated) was converted to the hollow hexagonal tube through some intermediate morphologies which are corresponding to particular crystal structures. Here, we have established a strong correlation between crystal structures with the morphology. These hollow tubes have been employed for Rhodamine B dye adsorption studies and showed an uptake of 82%, much more significant than Form I (interpenetrated) (39%) due to the presence of a pore channel in the crystal structure.
Keywords: dye adsorption; hollow hexagonal rod; hydrogen-bonded organic framework; morphology evaluation; trimesic acid

Multicomponent solvate crystals of 3,5-dinitrobenzoic acid and acetamide and CSD analysis of solvates - Shaikh, Tabrez Rafique; Shelke, Nikita; Tothadi, Srinu (ACS Omega, 2023)
Twelve multicomponent solvate crystals (cocrystal solvates) of 3,5-dinitrobenzoic acid and acetamide were synthesized via slow evaporation method. All crystalline materials were characterized by single-crystal X-ray diffraction. All cocrystal solvates are isostructural, and crystal packing forms continuous channels where some solvent molecules are connected via weak intermolecular interactions with 3,5dinitrobenzoic acid and acetamide. All multicomponent solvate crystals encompass amide-amide dimer homo synthons and form R22 (8) motifs. Moreover, the phase purity of solvate crystals was analyzed by powder Xray diffraction. Further, most of the cocrystal solvates were analyzed by nuclear magnetic resonance and differential scanning calorimetry. Cambridge structural database analysis categorizes solvate propensity in single-crystal structures. The importance of hydrogen bond donor/ acceptor nature, size, and shape of solvents is also discussed in the context of crystallization and crystal packing.
Keywords: Co-Crystals; Design; Host Guest Complex; solvent